Purification of Crude Glycerol from Acidification Using Tea Waste. (July 2018) - Aziz, Isalmi; Sulistina, Rara Citra; Hendrawati,; Adhani, Lisa
Abstract: Biodiesel production generates crude glycerol with low purity as a byproduct. It must be purified to increase the economic value of glycerol. Purification can be performed using adsorbent from tea waste. This study aimed to examine the optimum condition of adsorption process, characterize the biosorbent from tea waste and determine the quality of purified glycerol. Crude glycerol was produced by transesterification reaction of used cooking oil with methanol using KOH as a catalyst. The reaction temperature was 60°C which was maintained for 60 minutes.Crude glycerol was separated from biodiesel and added with H3 PO4 85% untilthe pH reached ±2.5. Glycerol level after acidification was 77%. After that, adsorption was performed using tea waste which was previously activated by 0.05 M NaOH. Adsorption process was conducted by varying contact time (30, 60, 75, 90 and 120 minutes), adsorption temperature (30, 45, 60 and 75°C), biosorbent concentration (6, 9, 12, 15 and 18 %) andbiosorbent particle size (180, 250 and 630 μm). The highest glycerol level (95.9544%) was achieved by setting the contact time for 90 minutes, adsorption temperature at 60°C, biosorbent concentrationat 12% andparticle sizeat 180 μm. The glycerol obtained from this process meets the quality requirements set bySNI06-1564-1995with water content3%, ash content0.3% andMONG level 0.7%. In addition, the purifiedglycerol had density 1.26 g/mL, potassium metal content 107 ppm andhad no sugar.There were alterations in functional group and surface morphology of tea waste after the adsorption took place.